Synthesis of Some New 3,4/4,6-Disubstituted- 1,2,4-Trianine-5-Ones Bearing a Pyrazoleo-Pyridazine Moiety - Fawzy, M.M.; Abdel-Rahman, R.M.; El-Gendy, Z. (Asian Journal of Chemistry, 2010)
The synthesis of3,4-disubstituted-6-dihydro-1 ,2,4-triazine-5(H) one (IV), 4,6-disubstituted-1,2,4-triazine-5 (3H) ones (IX), 4,5,6-trisubstituted-3,5-dihydro-1,2,4-triazine(XII), 4,6-disubstituted-3H-5-dihydro-1,2,4-triazine (XIII) and 4-substituted-1,3,5,6-hexahydro-1,2,4-triazine(XIV) have been accomplished starting from α-hydrazinocarboxamide III and formyl-hydrazone VIII by the reaction with acid halides, α-oxoacids, α-haloketones and α,β-bihalocompounds. The structure of all new prepared compounds were elucidated on the basis of chemical and spectroscopic data.